Graphical vs. nongraphical displays: which one is the best labeling system for laboratory searching task? - Mohd Zamri, Muhamad Zul Asraf; Adnan, Ammar; Radin Umar, Radin Zaid; Samuel, Siby; Shaffiar, Norhashimah; Abdul Hamid, Abd. Malek (Human factors and Ergonomics Society Malaysia, 2018)
Graphical displays are known to improve the process of obtaining information because it can be easily comprehended. It also can be recognized faster and more precisely compared to nongraphical (i.e. alphanumerical) displays. However, it is unknown if the graphical displays application in labeling systems can improve the human performance in searching tasks in general, more particularly, on reducing the completion time of searching tasks and minimizing the errors made during the laboratory searching task. The objectives of the study are: (i) to evaluate the effect of graphical displays on the completion time of searching tasks; and (ii) to evaluate the effect of graphical displays on the errors made during searching tasks. Thirty-two participants (M= 21.875 years old; SD = 1.453) were recruited for the study, and assigned evenly to either the Graphical or the NonGraphical group. Participants were instructed to search for a total of sixteen items in a laboratory, and the completion time and errors made by him or her were recorded. The findings show that: (i) in term of completion time, there was a significant difference in the performance for Graphical group (M = 743.59, SD = 103.57) and NonGraphical group (M = 985.26, SD = 345.50) conditions; t (16) =2.680, p =0.015; and (ii) in term of the errors made, there was a significant difference in the performance for Graphical group (M = 0.19, SD = 0.544) and NonGraphical group (M = 1.13, SD = 1.360) conditions; t (16) =2.560, p =0.019. The results show that graphical displays is the best labeling system for laboratory searching task for both dependent variables being evaluated. The results from this study provide additional information regarding the application of graphical displays on human performance in general, and more specifically, recommend a better and suitable display type of labeling system – which is, one of the attributes of 5S system – for searching tasks.